Association of the lupus low disease activity state (LLDAS) with health-related quality of life in a multinational prospective study - Vera Golder (2018)
© 2017 The Author(s). Background: Systemic lupus erythematosus (SLE) is associated with significant impairment of health-related quality of life (HR-QoL). Recently, meeting a definition of a lupus low disease activity state (LLDAS), analogous to low disease activity in rheumatoid arthritis, was preliminarily validated as associated with protection from damage accrual. The LLDAS definition has not been previously evaluated for association with patient-reported outcomes. The objective of this study was to determine whether LLDAS is associated with better HR-QoL, and examine predictors of HR-QoL, in a large multiethnic, multinational cohort of patients with SLE. Methods: HR-QoL was measured using the Medical Outcomes Study 36-item short form health survey (SF-36v2) in a prospective study of 1422 patients. Disease status was measured using the SLE disease activity index (SLEDAI-2 K), physician global assessment (PGA) and LLDAS. Results: Significant differences in SF-36 domain scores were found between patients stratified by ethnic group, education level and damage score, and with the presence of active musculoskeletal or cutaneous manifestations. In multiple linear regression analysis, Asian ethnicity (p < 0.001), a higher level of education (p < 0.001), younger age (p < 0.001) and shorter disease duration (p < 0.01) remained significantly associated with better physical component scores (PCS). Musculoskeletal disease activity (p < 0.001) was negatively associated with PCS, and cutaneous activity (p = 0.04) was negatively associated with mental component scores (MCS). Patients in LLDAS had better PCS (p < 0.001) and MCS (p < 0.001) scores and significantly better scores in multiple individual SF-36 domain scores. Disease damage was associated with worse PCS (p < 0.001), but not MCS scores. Conclusions: Ethnicity, education, disease damage and specific organ involvement impacts HR-QoL in SLE. Attainment of LLDAS is associated with better HR-QoL.